Propozycja metody identyfikacji dysproporcji w rozwoju regionów w Polsce i Unii Europejskiej - Rozkrut, Monika (The Proposal of the Method of Identification of Disproportions in Regional Development in Poland and the European Union, 2006)
Regional and cohesion policy plays essential role in the European Union, occupying important position among its aims. Monitoring of these policies' efficiency becomes a very significant problem. The monitoring is a difficult process, but very essential from point of view of efficiency appraisal. Insufficiently developed monitoring system was one of the weaknesses of structural policy in its initial phase. The author tries to make a contribution to the problem by presenting in this article the procedure allowing appraisal of socio-economic cohesion of EU regions with use of statistical methods of ordering and grouping. The description of the procedure and empirical example is presented in the paper. The example concerns Polish NUTS 1 regions. Presented methods are used for the appraisal of regions from the point of view of development as well as to classify with regard to similarities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 302-309